Implementasi Pengendalian Kualitas Produk Sepatu Wanita Menggunakan Metode Failure Mode Effect Analysis (FMEA) dan Fault Tree Analysis (FTA) pada Home Industry Vielin Creation Bandung - Dewi, Marissa Puspa; Azis, Anton Mulyono (Banking & Management Review, 2019)
This research was conducted in Vielin Creation Home Industry to find out how to control the quality of ladies’s shoes product, identify factors causing defect in product and apply product quality control using Failure Mode Effect Analysis (FMEA) method and Fault Tree Analysis (FTA) method to solve existing problems. The used method in this research is Failure Mode Effect Analysis (FMEA) and Fault Tree Analysis (FTA), which is integrated with other quality analysis tools that is, Fishbone Diagram to identify factors of causing defects of shoes products in Vielin Creation.From the results of this research obtained 17 potential failure modes from 7 existing processes. Then got 2 RPN value that exceeds critical number 100 that machine often jam with RPN 315 and glue has not sealed perfectly with RPN 180. Then both modes of failure are processed using Fault Tree Analysis (FTA) method and obtained the root cause of both modes of failure. From each root cause cause is then given the proposed improvement for the company in overcoming the existing problems. Keywords: Quality Control, Failure Mode Effect Analysis (FMEA), Fault Tree Analysis (FTA)